EKSPLOITASI PEKERJA ANAK DI DESA DANAU LANCANG KECAMATAN TAPUNG HULU - Rahman Hidayat; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Exploitation of Child Labor in Indonesia refers more to the situation in the form of a lack of matters relating to the fulfillment of primary needs, such as clothing, food and shelter. This poverty problem affects many things, including unemployment, crime, and no less important poverty has an impact on the deprivation of children's rights. The observed environmental aspects of exploitation are: Overview of economic conditions, Population Livelihoods, Land Use, Socio-Cultural Conditions. Problems taken from this research are: (1) What is the form of exploitation of child labor in Tapung Hulu District ?, (2) What are the factors driving the exploitation of child labor in Tapung Hulu District ?. This study aims: (1) To find out the form of exploitation of child labor in Tapung Hulu District ?, (2) To analyze the factors driving the exploitation of child labor in Tapung Hulu District ?. The locations of this research are: Lake Lancang Village in Tapung Hulu Subdistrict, Kampar District. The method used is descriptive qualitative method. The population in this study is the people who live in the village of Lake Lancang, Tapung Hulu District. Data collection techniques, namely the method of observation, interviews, documentation. The results of the study explain that: exploitation of child laborers in the village of Lake Sancang is largely based on educational and economic factors, so that the abuse of child labor to be employed for the benefit of their parents or others such as child laborers works and leads children to work that should not have been undertaken. Key Word : Children's ExploItation